Respostas ao défice hídrico em feijão (Phaseolusvulgaris) e caupi (Vigna unguiculata), induzidas poróxido nítrico - Lucas Martins Zimmer Prados (2007)
Nitric oxide (NO) is recognized as an intra and inter cellular mediator of anumber of functions in animal and vegetal cells. Some authors consider it as astress inductor agent and some claim it has a protective role acting, mainly, in theinterruption of free radical chains formed under stress conditions. Among thelimiting factors to plant growth, water stress is considered the greatest. Its effectsare usually seen as low photosynthesis and growth rates, frequently associatedwith disturbances in plant metabolism. To analyze the effects of NO in water stressconditions, seeds and plants of Phaseolus vulgaris and Vigna unguiculata,respectively sensitive and tolerant to stress, were submitted to severe droughtconditions with and without NO exogenous application via sodium-nitroprussiate(SNP). Seed germination, stomatal conductance (GS), photosynthetic parameters(electron transport rate (ETR) and maximum yield (FMax)), and relative watercontent (CRA) were analyzed. Electrolyte leakage (FE) and membrane injury index(IDM) were measured in detached portions under controlled stress conditions byusing polietilene glycol (PEG-6000) solutions. In PEG Treated plants, NO wasresponsible for a significative increase of 37% for P. vulgaris and 50% for V.unguiculata in seed germination rates when compared to the groups that didntreceive SNP, 11% and 15% respectively. It was also responsible for a delay inphysiological death, 24h for V. unguiculata and 48h for P. vulgaris, of thestressed individuals, evident by the minimum GS, ETR, FMax and CRA valuesfound when compared to the control groups. NO had no influence over IDM databeing those directly proportional to the stress level which plants were submittedto. Though, P. vulgaris, sensitive to drought, had a more pronounced effect. ELwas higher during the first 15 minutes of washing, established in previous essaysbut also had no correlation with exogenous NO application. In detached portions,NO had a positive effect on photosynthetic values increasing ETR under moderatestresses, hidric potentials (ØW) -0,6MPa for P. vulgaris and -0,9MPa for V.unguiculata. Under severe drough conditions, (ØW) -1,2MPa for P. vulgaris and -1,8MPa for V. unguiculata, NO decreased ETR values when compared to theplants that didnt receive exogenous SNP. It was concluded that there is a positiverelation between the application of NO and a delay of the negative effects ofdrought, a beneficial interaction between NO and seed germination under induceddrought stress and an increase of drought resistance in both tolerant and sensitiveplants.